Drosophila neuropeptides in regulation of physiology and behavior - Nässel, Dick R; Winther, Asa M E (Progress in neurobiology, 2010)
Studies of neuropeptide and peptide hormone signaling are coming of age in Drosophila due to rapid developments in molecular genetics approaches that overcome the difficulties caused by the small size of the fly. In addition we have genome-wide information on genes involved in peptide signaling, and growing pools of peptidomics data. A large number of different neuropeptides has been identified in a huge variety of neuron types in different parts of the Drosophila nervous system and cells in other locations. This review addresses questions related to peptidergic signaling in the Drosophila nervous system, especially how peptides regulate physiology and behavior during development and in the mature fly. We first summarize novel findings on neuropeptide precursor genes, processed bioactive peptides and their cognate receptors. Thereafter we provide an overview of the physiological and behavioral roles of peptide signaling in Drosophila. These roles include regulation of development, growth, feeding, metabolism, reproduction, homeostasis, and longevity, as well as neuromodulation in learning and memory, olfaction and locomotor control. The substrate of this signaling is the peptide products of about 42 precursor genes expressed in different combinations in a variety of neuronal circuits or that act as circulating hormones. Approximately 45 G-protein-coupled peptide receptors are known in Drosophila and for most of these the ligands have been identified. Functions of some peptides are better understood than others, and much work remains to reveal the spectrum of roles neuropeptides and peptide hormones play in the daily life of a fly.